Sensitivity analysis of Malaysian highway capacity manual for unsignalised intersections - Izzian, Izzuddin. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Unsignalised intersections play an important role in determining capacity of road network. Two major parameters used in unsignalised intersection analysis are critical gap and follow - up time. There are several factors affecting the critical gap and the fol low - up time such as vehicle composition, intersection geometry, major street traffic volume, minor street delay, minor stream approach grade, and others. In this research, the critical gap and the follow - up time were analyzed based on vehicle type, specifi cally passenger car an d motorcycle. C ritical gap estimations were based on the Maximum Likelihood method . T hese two major factors will be use d to estimate the level of service and capacity of unsignalised intersections. Malaysian Highway Capacity Manual (M HCM) was produced based on the traffic condition in We st Malaysia. The study is to find out the application of MHCM in Sarawak. Sensitivity analysis is being carried out by using MHCM 2006.